Design of Batik Dhemar Kambhang Information Media Based on Observational Documentary Film - Ahmad Walid Hujairi; Khoironi Khoironi; Ahmed David Anugerah (Publikasi Indonesia, 2025)
Dhemar Kambhang Batik is a typical batik from Sumenep Regency, Madura, which has a unique motif and deep philosophy, namely as a